Motivation Role in Improving Work Effectiveness - Yeti Kuswati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
In an effort to realize the vision of the Regional Technical Implementation Unit (UPTD) of Irrigation Network at Talaga, Majalengka, which is "providing optimal and maximum service in the field of irrigation to the public", it is needed a motivation from the Head of the UPTD so that employees can actively and enthusiastically carry out management, utilization, and services of irrigation. Based on observations, it turned out that the effectiveness of employee's work in irrigation management is still not optimal (still low). The problem was because the implementation of motivation by Head of the UPTD is not based on the principles of motivation maximally. This research was conducted at the UPTD of Irrigation Network at Talaga, Majalengka, using a theoretical basis on motivation with the parameters of principles of motivation proposed by Malayu S.P. Hasibuan and for the measurement of work effectiveness using indicators according to Gibson which are production, quality, efficiency, flexibility, and satisfaction. The analytical method used was a quantitative analysis method using quantitative descriptive analysis techniques, scoring, and crosstab. In this study, the sample used was random sampling.